MENJELAJAHI DIRI DENGAN TEORI KEPRIBADIAN CARL R. ROGERS - Lia Amalia (Universitas Muhammadiyah Ponorogo, 2013)
Central to Rogers personality theory is the notion of self or self-concept. This is defined as the organized, consistent set of perceptions and beliefs about oneself. Rogers believesd that we need to be regarded positively by others. We need to feel valued, respected, treated with affection and loved. Positive regard is to do with how other people evaluate and judge us in social interaction. Rogers made a distinction between unconditional positive regard and conditional positive regard. Unconditional positive regard is where parents, significant others accepts and loves the person for what he or she is. Positive regard is not withdrawn if the person does something wrong or makes a mistake. Rogers believed that every person could achieve their goal wishes, and desires in life. When they did so self actualisation took place. For Rogers people who are able be self actualise are called fully functioning persons. This means that person is in touch with the here and now, his or her subjective experiences and feelings, continually growing and changing.